PENGINTEGRASIAN PENDIDIKAN PENCEGAHAN HIV AIDS DALAM SATUAN PROGRAM PENDIDIKAN NONFORMAL DAN INFORMAL - Kusmiadi, Ade (JIV-Jurnal Ilmiah Visi, 2008)
Community Learning Center (CLC) is a strategic place for various community learning activities that focus on potency empowerment to mobilize development in education, social, economy, and culture including HIV AIDS prevention. Unfortunately, a few CLCs carry out the prevention education of HIV AIDS. This article provides a guide for educational and non-educational personnels in CLC/PKBM to carry out the integration of HIV AIDS prevention education either into CLC’s activities or subject matters within courses and youth programs. They are expected to be able to improve their skills in integrating HIV AIDS education prevention and taking a part to combat stigma and discrimination.